2021
DOI: 10.3390/jcm10194429
|View full text |Cite
|
Sign up to set email alerts
|

Parameters Affecting the Retention Force of CAD/CAM Telescopic Crowns: A Focused Review of In Vitro Studies

Abstract: Telescopic systems constructed using computer aided design and computer aided manufacture (CAD/CAM) can overcome many drawbacks associated with conventionally constructed ones. Since retention is considered the most important function of these retainers, this scoping review aimed to discuss and summarize the parameters that affect this function in CAD/CAM-manufactured telescopic crowns and to compare their retention force values with the recommended retention force. An electronic search was done in Pubmed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Interestingly, the study by Kamel et al, [22] agreed the findings of the current study which evaluated the performance of telescopic crown material combination, including PEEK-PEEK, PEEK-ZrO2, and PEEK-CoCr. In contrast to the other groups, they noticed that the PEEK-PEEK crown combination experienced the highest retention force.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, the study by Kamel et al, [22] agreed the findings of the current study which evaluated the performance of telescopic crown material combination, including PEEK-PEEK, PEEK-ZrO2, and PEEK-CoCr. In contrast to the other groups, they noticed that the PEEK-PEEK crown combination experienced the highest retention force.…”
Section: Discussionsupporting
confidence: 91%
“…However, using a Zirconia or PEKK main crown is a good choice if a metalfree procedure is intended. 51 Milling was used for fabrication the frameworks and the primary crowns as it minimizes fabrication flaws in the dental prostheses. Milling excludes waxing, investing, and casting of the prosthesis which improve the overall precision.…”
Section: Discussionmentioning
confidence: 99%
“…However, the combination of zirconia with non-precious alloy secondary crowns has been reported to cause significant wear and loss of friction [ 5 ]. Studies testing zirconia as a secondary crown material have reported contradictory findings [ 14 ], and further studies are necessary for more accurate results and for providing reliable recommendations.…”
Section: Introductionmentioning
confidence: 99%